DAMPAK PAPARAN KONTEN YOUTUBE DAN TIKTOK TERHADAP PERKEMBANGAN BAHASA INDONESIA ANAK SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Nala Kania; Siti Aisyah; Anggun Nur Andiany; Easter Simanjuntak; Indah Nurmahanani (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2026)
Abstract The increasing consumption of digital content among elementary school-aged children raises fundamental questions about its impact on Indonesian language development. International evidence from Scopus-indexed studies consistently shows that excessive screen exposure negatively associates with children's vocabulary and pragmatic development (Toth et al., 2026; Sundqvist et al., 2024), while content quality and parental mediation emerge as key moderating factors (Yang & Guan, 2024; Romano et al., 2025). This study is a systematic literature review (SLR) employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol to systematically examine the influence of digital content viewing habits particularly through YouTube and TikTok on children's language competencies, encompassing vocabulary development, speaking ability, listening comprehension, and social communication. A three-database search (Google Scholar, Sinta, Scopus) yielded 127 initial articles, which were reduced to 12 eligible sources through four PRISMA selection phases (identification, screening, eligibility, inclusion). Analysis was conducted through narrative synthesis based on thematic categorization. Findings reveal a dual impact of digital content: educational and directed content demonstrably enriches vocabulary and improves speaking skills, while unmonitored entertainment content promotes non-standard language use, slang imitation, and reduced quality of direct verbal interaction. Key determinants of impact direction include content quality, exposure intensity, and active parental involvement. This study recommends integrated digital literacy strategies involving parents, educators, and policymakers.